Organizational Culture, Work Environment, and Workload on the Performance of POLRI Members (Case Study in Pekanbaru Police Criminal Reserve Unit) - John Rafizal; Nyoto; Sudarno; Fazal Mohamed Mohamed Sultan (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to determine and analyze the influence of organizational culture, work environment, and workload on job satisfaction and performance of the Pekanbaru Police Criminal Investigation Unit. The number of samples in this study was the entire population of the study as many as 79 personnel of the Criminal Investigation Unit of the Pekanbaru Police. Data collection techniques with Interval. This study uses SEM PLS Models. The results show that organizational culture has a negative but not significant effect on job satisfaction, the work environment has a positive but not significant effect on job satisfaction and workload has a positive but not significant effect on job satisfaction of the Criminal Investigation Police personnel. Pekanbaru. But organizational culture has a positive and significant effect on job satisfaction, the work environment has a positive and significant effect on performance and workload has a positive and significant effect on the performance of the Pekanbaru Police Criminal Investigation Unit. While job satisfaction has a positive but not significant effect on the performance of the Pekanbaru Police Criminal Investigation Unit.